A short history and some results of the dermatoglyphic studies in Hungary - Gyenis Gyula (Acta biologica Szegediensis, 2000)
Dermatoglyphics began with dactyloscopy in Hungary in the early 1900s. Since then, the interest in several fields of dermatoglyphics has arisen, e. g. paleodermatoglyphics, heredity of the dermatoglyphic traits, dermatoglyphics in medical disorders, dermatoglyphics of different populations in Hungary, dermatoglyphics in questioned paternity as well as the study of the palmar and plantar creases. Due to the numerous studies published in these fields, it is impossible to list all of them, therefore this paper highlights only the results of some of them.Dermatoglyphics began with dactyloscopy in Hungary in the early 1900s. Since then, the interest in several fields of dermatoglyphics has arisen, e. g. paleodermatoglyphics, heredity of the dermatoglyphic traits, dermatoglyphics in medical disorders, dermatoglyphics of different populations in Hungary, dermatoglyphics in questioned paternity as well as the study of the palmar and plantar creases. Due to the numerous studies published in these fields, it is impossible to list all of them, therefore this paper highlights only the results of some of them.